Students’ Self-Regulated Learning in English Classroom - Melda Yeni; Maizarah Maizarah; M. Ridhwan (Universitas Lancang Kuning, 2021)
This paper aims to explore English students’ self-regulated learning and its factors. A quantitative survey method using total sampling techniques was administered toward 118 eleventh-grade students of SMAN 1 Tembilahan Hulu-Riau. The data were collected directly using a Likert scale questionnaire derived from a careful examination of the works of literature. The data then analyzed using a descriptive mean formula and further interpreted qualitatively to answer the formulated questions. The results showed that students’ self-regulated learning in the English classroom is at the “enough” level. This result was influenced by four factors, namely: The support of environment, technology, confidence, and a desire to learn independently.